2020
DOI: 10.1021/acs.jafc.0c00731
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Optimization Strategy Based on the Perfect Conformation of Prolyl Endopeptidase for Improving Catalytic Efficiency

Abstract: Prolyl endopeptidases (PEPs) hydrolyze proteins to yield bioactive peptides and are effective in the treatment of celiac disease. However, the catalytic efficiency of PEPs still has the potential to be improved, which could further strengthen their industrial and therapeutic applications. Herein, a novel rational design strategy based on a "near-attack conformation" of the catalytic state of PEP was adopted. Constrained dynamic simulations were applied, followed by the virtual screening of potentially favorabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…APE is a prolyl endopeptidase that can hydrolyze the peptide bond of proline residue in the substrate and expose proline residue via launching a "nucleophilic attack" on the C of proline residue in the substrate by the O of serine residue of the APE active center. 18 The exposed proline residue in the broken substrate became easier to be hydrolyzed by other proteases in soy sauce moromi, which was the reason for a higher proline content determined in the sample. Based on the above analyses, it can be concluded that APE has the capability to degrade proteins rich in proline residues whether under salt-free condition (beer) or high-salt condition (soy sauce).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…APE is a prolyl endopeptidase that can hydrolyze the peptide bond of proline residue in the substrate and expose proline residue via launching a "nucleophilic attack" on the C of proline residue in the substrate by the O of serine residue of the APE active center. 18 The exposed proline residue in the broken substrate became easier to be hydrolyzed by other proteases in soy sauce moromi, which was the reason for a higher proline content determined in the sample. Based on the above analyses, it can be concluded that APE has the capability to degrade proteins rich in proline residues whether under salt-free condition (beer) or high-salt condition (soy sauce).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In a recent work, Li X. and co‐workers managed to improve the activity of a prolyl endopeptidase by tuning interactions with mutations, thus stabilizing the “perfect” reactive conformation. The Ile462Trp and Gln560Tyr mutants displayed an increase in enzymatic efficiency in 32.7 % and 6.3 %, respectively [41] …”
Section: Enhancements Of the S‐norcoclaurine Biosynthesis Enzymesmentioning
confidence: 99%
“…The Ile462Trp and Gln560Tyr mutants displayed an increase in enzymatic efficiency in 32.7 % and 6.3 %, respectively. [41] Ferreira and co-workers have also studied the influence of mutating active site residue Thr62 by 18 different amino acid residues in a NADH-FMN oxidoreductase. The results suggest that mutation by an aspartate residue lowered the activation of free energy in about 10 kcal/mol in relation to the wild-type to a 10 7 -fold increase of the k cat .…”
Section: Computational Alanine Scanning Mutagenesis and Rational Muta...mentioning
confidence: 99%
“…During the optimization, the distance between N-5 of FAD and C-4 of NMNH atoms is constrained so that the substrate is in a catalytic conformation. 27 The structure of the wild type is optimized using the same method. The molecular mechanics/generalized Born surface area (MM/GBSA) 28,29 method is subsequently adopted to calculate the binding free energy of protein and substrates based on the optimized structure obtained aer mutation.…”
Section: Computer Virtual Mutationmentioning
confidence: 99%